Optimalisasi Pembelajaran Pendidikan Agama Islam (PAI) melalui Metode Discovery Learning - Zaki Afnan Salmadatu; Syamsudin Syamsudin (At Turots: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to examine the utilization of 21st-century learning approaches in the context of Islamic Religious Education through the implementation of the discovery learning method. Moreover, it aims to present an overview of the educational enhancements achieved by implementing discovery learning, specifically in the field of Islamic Religious Education. The research methodology employed in this study is Library Research, adopting a qualitative approach. The researcher primarily focuses on the utilization of secondary data obtained from various sources such as books, journals, and relevant literature, regardless of their publication status. Data collection involves a thorough examination, analysis, and verification of concrete data pertaining to the research topic through a literature review. The findings of this study demonstrate that the discovery learning method provides students with opportunities to explore, acquire, process, map, and creatively discover new knowledge. In this context, the teacher plays a guiding role in facilitating the learning process. The implementation of the discovery learning method in Islamic Religious Education encompasses six stages: stimulus provision, problem identification, data collection, data processing, real-world validation, and drawing conclusions based on the obtained findings.